DESAIN LAPORAN KEUANGAN PADA ENTITAS PELAPORAN RUMAH SAKIT BERSTATUS BLUD (Studi Kasus pada Rumah Sakit Jiwa Menur Pemerintah Provinsi Jawa Timur) - Nanda Dwi Firdausi ; Yuki Firmanto, MSA., Ak (Akuntansi FEB - UB, 2018)
The aim this research is to find out the accountancy principle that is referred to by the reporting entity of hospital with BLUD (Regional Public Service Agency) status that designs financial statements based on SAK (Standar Akuntansi Keuangan) or Financial Affairs Accountancy Standard. The object of this research is the Menur Mental Hospital of the East Java Provincial Government. This research used the qualitative method with a case study approach. Research data were collected by interviews, observation, and documentation. The research findings indicated that the Menur Mental Hospital uses East Java Government Regulation Number 2 of Year 2017 as the accountancy principle reference which is still based on SAP (Standar Akuntansi Pemerintah) or Government Accountancy Standard. The financial statement design that is suggested by researcher with the accountancy principle referring to SAK ETAP leads to several differences with the financial statements for which the accountancy principle refers to East Java Government Regulation Number 2 of Year 2017. Keyword: Financial Statements, BLUD, SAK